Assessment of heavy metal accumulation in Penaeus monodon and its human health implications. (March 2023) - Acharya, Prasannajit; Muduli, Pradipta R.; Das, Mira
Abstract: Asian tiger shrimp Penaeus monodon ( P. monodon ) of Chilika lagoon, India was studied regarding the metal accumulation and its associated human health risks. It showed a tendency of metal accumulation in the following order: Zn > Ni > Cu > Co > Cr > Pb > Cd. A two-way ANOVA indicated the metal accumulation was insignificant with respect to season ( n = 421, p = 0.59) and sector ( n = 32, p = 0.61). The estimated daily intake (EDI), targeted hazard quotient (THQ) and hazard index (HI), and carcinogenic risks (CR) revealed no potential human health risks and were safe for consumption. The pollution load index (PLI) of <1, Geo-accumulation index (Igeo, ) and contamination factor (CF) indicated that the study area was unpolluted. This pioneering study highlighted that P. monodon was nurtured well in the healthy habitat of Chilika lagoon and the fair level of metal content made it an excellent source of dietary components. Highlights: Chilika water and sediment are safe habitats for Penaeus monodon. Penaeus monodon of Chilika lagoon safe for human consumption. Metal accumulation in Penaeus monodon is within the threshold range.